Coronado-era Place-names, II. "Chichilticale" and the Origin of the Name of the "Chiricahua" Mountains. Issue 1 (2nd January 2016) - Hartmann, William K.; Fabián, Constantino Martínez
Abstract : A Coronado-era name, variously spelled as "Chichiltecally, " "Chichilticale, " etc., was applied in 1540 to a mountain range, a ruin, and the surrounding area in southeast Arizona. Today it is usually described as a Nahuatl word assigned to a red-colored pueblo ruin on the Coronado route to Cíbola. We note, however that the chronicler Jaramillo, with the lead portion of the Coronado expedition, assigned "Chichiltecally" solely to a mountain range and associated pass. Recent archaeological finds indicate that the ruin was at the west base of the Chiricahua Mountains and south of Apache Pass. We show that the name recorded by Jaramillo was an attempt to render an Ópata term connoting "Mountain Range of Many Turkeys, " and that this name evolved through various spellings to "Chiricahua, " which essentially means "Turkey Mountain." Application of a similar Nahuatl term to the ruin may have arisen from a misunderstanding or adaptation of the Ópata term by Nahuatl speakers on the Coronado expedition, or it may have been interpreted as the "correct" native name after the chroniclers returned to the Nahuatl-dominated Mexico City area.